Serum Cystatin C as a Predictor of Acute Kidney Transplant Rejection - Shamkhi, Fadhil B.; Ali, Ala Sh.; El-Yassin, Hedef D. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Accurate and rapid assessment of allograft function is essential. Cystatin C has recently been proposed as an alternative marker of glomerular filtration rate (GFR). Its diagnostic value for the longitudinal assessment of graft function has not been addressed well.Objective: To study the validity of cystatin C as an early marker and predictor of acute transplant rejection in the first week post transplantation.Subjects and Methods: Sixty six renal transplants recipients recruited. The study conducted in four renal transplantation centers in Baghdad for the period from September to December 2011. Serum creatinine and cystatin C concentrations measured 48 hours before transplantation and day 3 and 7 post transplantation.Results: Serum Cystatin C observed to significantly increased at day 3 (p